2021
DOI: 10.1002/jctb.6943
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of nitrifying sludge supplemented with 2‐chlorophenol in SBR reactors

Abstract: BACKGROUND The metabolic improvement and reduction of the inhibitory effect of 2‐chlorophenol (2‐CP) on the nitrification process occurring in nitrifying SBR systems can be associated with changes in the microbial community. The physiologic, kinetic, and microbial population behaviors of two nitrifying sludges were evaluated in two parallel sequencing batch reactors (SBR1 and SBR2) amended with 2‐CP. Seven cycles were performed with 20 to 60 mg 2‐CP‐C/L. RESULTS Ammonium‐oxidizing and nitrite‐oxidizing process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…In this study, the authors presented the optimization of the support material diameter and bed porosity. Martínez‐Jardines et al 10 . reported the metabolic improvement and reduction of the inhibitory effect of 2‐chlorophenol on nitrification processes performed in sequencing batch reactors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the authors presented the optimization of the support material diameter and bed porosity. Martínez‐Jardines et al 10 . reported the metabolic improvement and reduction of the inhibitory effect of 2‐chlorophenol on nitrification processes performed in sequencing batch reactors.…”
mentioning
confidence: 99%
“…9 In this study, the authors presented the optimization of the support material diameter and bed porosity. Martínez-Jardines et al 10 reported the metabolic improvement and reduction of the inhibitory effect of 2-chlorophenol on nitrification processes performed in sequencing batch reactors. Likewise, Banda et al 11 performed physiological and kinetic evaluations of a denitrifying sludge using ampicillin as the only electron source, showing that denitrification processes allow the simultaneous oxidation of recalcitrant compounds and nitrate reduction during wastewater treatment.…”
mentioning
confidence: 99%